Комунікаційні Інтернет-ресурси для релігійних спільнот - Керенович, Лілія; Лісіна, Світлана (Видавництво Львівської політехніки, 2020)
This article presents the findings of a survey of religious internet communications. Also, the basic forms of web communications of religious organizations are considered.
Keywords: інформаційні ресурси; комунікація; Інтернет; релігійна організація